TELAAH HERMENEUTIKA DALAM KITAB TA’WIL MUKHTALIF AL-HADITS KARANGAN IBN QUTAYBAH - Muhammad Sakti Garwan (Faculty of Ushuluddin and Religious Studies UIN Sulthan Thaha Saifuddin Jambi, 2020)
This article examines the book Ta‟wil Mukhtalif al-Hadits, written by Ibn Qutaybah. This book is compiled in response to the political turmoil that occurred during his lifetime. Ibn Qutaybah also wanted to dispel the assumption that some groups who accused the scholars of hadith, had committed negligence, by narrating hadiths that are in conflict with each other that are not in line with the Qur‟an and the understanding of reason. This study uses the library method by making the book Ta‟wil Mukhtalif al-Hadits the primary source. In addition, the author uses the theory of hermeneutics as an analytical tool to categorize this book as a hermeneutic book of classical hadith. The results of the study stated that the book Ta‟wil Mukhtalif al-Hadits has its own characteristics in looking at the hadith that seem to be contradictory but in terms of meaning is not, and also he took excellent steps in completing a hadith of the Prophet Muhammad saw., in that method and step until the book Ta‟wil Mukhtalif al-Hadits is categorized as a hermeneutic book of classical hadith. Tulisan ini menelaah kitab Ta‟wil Mukhtalif al-Hadits, yang dikarang oleh Ibn Qutaybah. Kitab ini disusun sebagai respons tentang pergolakan politik yang terjadi pada masa beliau hidup. Ibn Qutaybah juga ingin menepis anggapan sebagian golongan yang menuduh ulama hadis telah melakukan kecerobohan dengan meriwayatkan hadis yang saling berlawanan yang tidak sejalan dengan al-Qur‟an dan pemahaman akal. Penelitian ini menggunakan metode kepustakaan dengan menjadikan kitab Ta‟wil Mukhtalif al-Hadits sebagai sumber primer. Selain itu, penulis menggunakan teori hermeneutika sebagai alat analisis untuk mengategorikan kitab ini sebagai kitab hermeneutika hadis klasik. Hasil penelitian menyatakan bahwa kitab Ta‟wil Mukhtalif al-Hadits mempunyai karakteristik tersendiri dalam melihat hadis-hadis yang kelihatan saling kontra namun pada segi maknanya tidak, dan juga beliau mengambil langkah-langkah yang sangat baik dalam penyelesaian suatu hadis Nabi Muhammad saw., dalam metode dan langkah itulah hingga kitab Ta‟wil Mukhtalif al-Hadits ini dikategorikan sebagai kitab hermeneutika hadis klasik.